Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 2 - 2.7 - Inverse Functions - 2.7 Exercises - Page 229: 71


$f^{-1} (x)=-x-2$ The domain of the function $f$ is: $(-\infty, \infty)$. The domain of the inverse of the function $f$ is: $[0, \infty)$.

Work Step by Step

We have $y=|x+2|=-x-2$ or, $x=-y-2$ or, $x+y=-2 \implies y=-x-2$ Replace $y$ with $f^{-1} (x)$. so, $f^{-1} (x)=-x-2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.